Analisis Hukum Islam Terhadap Praktik Jual Beli Makanan Dengan Sistem Prasmanan dan Dine in : Studi Kasus Kantin Ulul Albab UINSU Medan - Zahra Amalia Khairani; Fitri Ritonga (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This article aims to discuss buying and selling activities with the concept of an Honest Buffet and Canteen based on the perspective of Islamic Law in the Ulul Albab Canteen of UINSU Medan. This article describes the explanation of the practice of buying and selling with the concept of an Honest Buffet and Canteen, how the concept of buying and selling is in Islam, and an analysis of how the concept of a Buffet Canteen and Honest Canteen are based on an Islamic perspective. And to add to the accuracy data, the case study for the establishment was only a case study of the activities of the Buffet Canteen and the Honesty Canteen which took place at UINSU Sutomo, Medan.